Experience of frontline nurses who managed the COVID-19 crisis: A qualitative study - Moradian, Seyed Tayeb; Mahmoudi, Hosein (Frontiers in Public Health, 2023)
Background: The health system was challenged due to the COVID-19 pandemic. Nurses as a part of the health system are expected to manage themselves in a situation where everyone is in crisis and to be able to do their work in a quiet and calm manner. This study was conducted to show how Iranian nurses faced the COVID-19 crisis. Methods: In a qualitative content analysis study, 16 participants including 8 nurses, 5 supervisors, and 3 head nurses of a university hospital in Iran, Tehran were interviewed from March to April 2020. Using purposive sampling, nurses who were working with COVID-19 patients were included. Data were analyzed using the MAXQDA 10 software and codes were categorized based on similarities and differences. Finding: Data analysis revealed 212 codes. These codes were classified based on similarities and differences in 16 categories and then four main themes of "unpreparedness", "positive adaptation", "negative coping", and "reorganization” emerged. Conclusion: Since that nurses are at the frontline of the fighting the biological disasters, it is a good opportunity to demonstrate the role of nurses in reducing the burden of disease, as well as identifying problems and opportunities and planning appropriate interventions.